2012
DOI: 10.1002/jmv.23293
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and virological characteristics of hepatitis B or C virus co‐infection with HIV in Indonesian patients

Abstract: Hepatitis virus‐related liver disease increases substantially the mortality rate of patients with HIV on highly active antiretroviral therapy (HAART). Therefore, early diagnosis of hepatitis B virus (HBV) and hepatitis C virus (HCV) is important. However, the prevalence of HBV and HCV infection in Indonesian patients infected with HIV is unknown. Therefore, this study examined the molecular and clinical characteristics of HBV and HCV in 126 patients infected with HIV, mostly on HAART, at Dr. Sardjito Hospital,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…In contrast to these reports, we observed a low prevalence of HCV and GBV-C infection among CSWs in Surabaya (Table 3). This discrepancy may be because most CSWs involved in this study were not IDUs (Table 1), whereas 44.4–62.7% of HIV-infected individuals involved in previous studies were IDUs [27], [28]. Our and previous results were consistent with reports that HCV and GBV-C mainly transmit through the sharing of needles and syringes, rather than through sexual contact [33], [34], [35], [36].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In contrast to these reports, we observed a low prevalence of HCV and GBV-C infection among CSWs in Surabaya (Table 3). This discrepancy may be because most CSWs involved in this study were not IDUs (Table 1), whereas 44.4–62.7% of HIV-infected individuals involved in previous studies were IDUs [27], [28]. Our and previous results were consistent with reports that HCV and GBV-C mainly transmit through the sharing of needles and syringes, rather than through sexual contact [33], [34], [35], [36].…”
Section: Discussionsupporting
confidence: 77%
“…We consider that such a high prevalence of anti-HBc Ab might be due to the low awareness of STDs and the high-risk behavior of CSWs for HBV infection, such as an unprotected sex with clients. In addition, previous reports showed that the prevalence rates of HBsAg and anti-HBc Ab were 3.2–15.3% and 30.2% among HIV-infected individuals in Indonesia, respectively [27], [28]. Our results revealed no HIV/HBV co-infection (anti-HIV Ab and HBsAg double positive), in spite of the high prevalence of anti-HBc Ab among CSWs (Table 3).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…The double infection is rather frequent, due to common routes of transmission [2,35-37], and liver disease is the second leading cause of death in patients infected by HIV [38]. …”
Section: Discussionmentioning
confidence: 99%
“…Indonesia is a multiethnic country with as many as 24 HBV subgenotypes, of which HBV subgenotype B3 (HBV/B3) is dominant [Nurainy et al, ; Mulyanto et al, ; Utsumi et al, ]. At least 15 subgenotypes of HCV have been identified throughout Indonesia, of which HCV/1b is the most prevalent [Hotta et al, ; Widjaja et al, ; Soetjipto et al, ; Tokita et al, ; Inoue et al, ; Utama et al, ; Anggorowati et al, ]. Nevertheless, few data exist for hemodialysis patients.…”
Section: Introductionmentioning
confidence: 99%